Evaluating the Level of Application of the Learning Organization Model in Enterprises in Kon Tum Province - Thi Thanh Truc, Phan (VNU Journal of Science: Policy and Management Studies, 2022)
The learning organization aims to create an open cultural environment in which employees self-study to improve their abilities while also support other colleagues in their development. The article conducted a survey of 204 employees at businesses in Kon Tum province and the results showed that psychological safety, respect for differences, openness to new ideas, time for reflection, education and training, information exchange, leadership reinforcement learning all ranked in the lowest group when compared to the standards of Harvard University. Towards this model, the article proposes a few solutions such as creating an open cultural environment where all employees can express their views openly, and it is necessary to introduce many policies to motivate employees to take initiative. Keywords Learning organization, employees, Kon Tum, culture. References [1] D. A. Garvin, Building a Learning Organization, Harvard Business Review, 1993, pp. 78-91. [2] D. A. Garvin, A. C. Edmondson, and Francesca Gino, is Yours a Learning Organization?", Harvard Business Review, Vol 86, No. 3, 2008, pp. 109-116. [3] P. Senge, The Leader's New Work: Building Learning Organizations, Sloan Management Review, Vol. 7, 1990, pp 7-23.